Frequency of and Risk Factors for Chronification in Traumatic Acute Subdural Hematoma following Conservative Therapy - Kaestner, Stefanie; van den Boom, Marina; Deinsberger, Wolfgang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background In an aging society, traumatic head injuries, such as acute subdural hematomas (aSDHs), are increasingly common because the elderly are prone to falls and are often undergoing anticoagulation treatment. Especially in advanced age, cranial surgery such as craniotomies may put patients in further jeopardy. But if treatment is conservative, a chronic subdural hematoma (cSDH) may develop, requiring surgical evacuation. Existing studies have reported a correlation between several risk factors contributing to the frequency of chronification. To improve the prediction of the course of disease and to aid counseling patients and relatives, this study aimed to determine the frequency and the main risk factors influencing the process of chronification of an aSDH following conservative treatment.Methods We identified patients presenting between January 2012 and September 2017 at our neurosurgical department with an aSDH. All patients treated conservatively were selected retrospectively, and the following parameters were documented: age, sex, chronification status, Glasgow Coma Scale score on admission and discharge, hematoma thickness and density, the degree of midline shift (MLS), prior anticoagulants and administration of procoagulants, thrombosis management, other coagulopathies, initial length of hospital stay, interval between discharge and readmission, and interval between initial injury and date of surgery and last follow-up. The cohort was divided into patients with complete resolution of their aSDH, and patients who needed surgery due to chronification.Results A total of 75 conservatively treated patients with aSDH were included. A chronification was observed in 24 cases (32%). The process of chronification takes an average of 18 days (range: 10–98 days). The following factors were significantly associated with the process of chronification: age (p = 0.001), anticoagulant medication (acetylsalicylic acid [ASA], Coumadin, and novel anticoagulants [NOACs]) before injury (p = 0.026), administration of procoagulants (p = 0.001), presence of other coagulopathies such as thrombocytopenia (p = 0.002), low hematoma density at discharge (p = 0.001), hematoma thickness on admission and discharge (p = 0.001), and the degree of MLS (p = 0.044).Conclusion Chronification occurred in a third of all patients with conservatively treated aSDH, on average within 3 weeks. The probability of developing a cSDH is 0.96 times higher with every yearly increase in age, resulting in 56% chronification in patients ≥ 70 years. Hematoma thickness and impairment of the coagulation system such as anticoagulant medication (ASA, Coumadin, and NOACs) or thrombocytopenia are further risk factors for chronification.
Keywords: acute subdural hematoma; chronification; risk factors; predictor; conservative treatment